2015
DOI: 10.1016/j.fob.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying NAD(P)H production in the upper Entner–Doudoroff pathway from Pseudomonas putida KT2440

Abstract: HighlightsThe first kinetic characterization of PputG6PDH-1 is presented.The relative production of NADH and NADPH by PputG6PDH-1 is quantified.The stoichiometric matrix of in silico metabolic models for Pseudomonas putida must be modified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…The rapid-equilibrium random ordered mechanism was the best model to explain the results observed in all cases, similarly to previous findings reported for the G6PDH-A isoform of strain KT2440 (19). Importantly, the main differences between G6PDH-A and G6PDH-B were detected in the K M values for NADP + and G6P, which indicate that the response of these enzymes to changes in the cytoplasmic concentrations of these metabolites could be different (Table 1) .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The rapid-equilibrium random ordered mechanism was the best model to explain the results observed in all cases, similarly to previous findings reported for the G6PDH-A isoform of strain KT2440 (19). Importantly, the main differences between G6PDH-A and G6PDH-B were detected in the K M values for NADP + and G6P, which indicate that the response of these enzymes to changes in the cytoplasmic concentrations of these metabolites could be different (Table 1) .…”
Section: Resultssupporting
confidence: 89%
“…Although most G6PDH are described as NADP + -dependent enzymes, previous reports suggested that dual or even NAD + -preferring homologues exist in several bacterial species, including Pseudomonas and close relatives (1719, 4244). The kinetic properties of the G6PDH-B and G6PDH-C isoforms present in strain KT2440 have not been studied so far, and whether G6P oxidation catalyzed by these variants would funnel electrons into the NADH or NADPH pools remains unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in activity mediated by each carbon source became more evident when analyzing the two major dehydrogenases of the oxidative PP pathway, i.e., glucose‐6‐ P dehydrogenase (Zwf) and gluconate‐6‐ P dehydrogenase (Gnd). These enzymes display a preference for NADP + as the cofactor (Olavarria et al ., ), and their capability to contribute NADPH under biodegradation conditions was clear: the Zwf activity increased three‐ and four‐fold in benzoate and m ‐xylene cultures as compared to that observed on citrate, and the Gnd activity augmented ca. three‐fold for the same comparison.…”
Section: Resultsmentioning
confidence: 95%
“…We thus measured the intracellular concentration of NADPH, as it is the redox cofactor that seemed to be over‐produced under biodegradation conditions. The NADPH concentration in exponentially‐growing KT2440 cells from glucose cultures was 276 ± 28 μM, consistent with previous reports (Chavarría et al ., ; Nikel et al ., ; Olavarria et al ., ). In citrate cultures, this value increased 1.8‐fold, reflecting the gluconeogenic demand of NADPH under these conditions.…”
Section: Resultsmentioning
confidence: 97%